Pengaruh Padat Tebar Terhadap Laju Pertumbuhan Ikan Patin (Pangasius pangasius) Effect of stocking density on the growth rate patin fish (Pangasius pangasius) - Andreas H Marpaung; Syammaun Usman; Indra Lesmana (AQUACOASTMARINE, 2017)
Patin fish is one of cultivication fish which familiar and have high economical price in Indonesia. Intensive cultivication can be done bya optimizing the stocking density. This research aims to determine optimum stocking density with an average length is 10 cm and weight is 5 gr. Patins are use as much as 324 fishes and maintenance container use are 9 aquariums with size 40 cm x 20 cm x 20 cm and the volume water are 12 liters each aquarium. The method use is Completly Randomize Design with the treatment of stocking density 1 fish/liter (P1); 3 fish/liter (P2); 5 fish/liter(P3). Ended treatment showed length P1 12,34 cm; P2 12,01 cm; P3 11,76 cm and weight P1 7,49 gr; ; P2 7,08 gr; P3 6,71 gr. Stocking density significantly affected on the length and weight growth rate.Keywords : Pangasius pangasius, patin, stocking density, growth rate